The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1442-9993.2011.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of historical forest contraction on the phylogeographic structure of Australo‐Papuan populations of the red‐legged pademelon (Macropodidae: Thylogale stigmatica)

Abstract: Geographic patterns of genetic variation are strongly influenced by historical changes in species habitats.Whether such patterns are common to co-distributed taxa may depend on the extent to which species vary in ecology and vagility. We investigated whether broad-scale phylogeographic patterns common to a number of small-bodied vertebrate and invertebrate species in eastern Australian forests were reflected in the population genetic structure of an Australo-Papuan forest marsupial, the red-legged pademelon (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Radiation of Melomys in Australia was estimated here to have occurred within the last 1.6 Myr, possibly corresponding with glacial cycles and associated shifts in vegetation prevalent in the late Plio‐Pleistocene (Hopkins et al ., ; Kershaw, ) and matches the timing of diversification observed in other taxa (e.g. Joseph & Moritz, ; Schneider et al ., ; Norman et al ., ; Krosch, ; Macqueen et al ., ). Frequent shifts in vegetation allowed range expansions in some taxa and caused range contractions and local population extinctions in others (Aplin, ; Martin, ; Lukoschek et al ., ; Bowman et al ., ; Byrne et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Radiation of Melomys in Australia was estimated here to have occurred within the last 1.6 Myr, possibly corresponding with glacial cycles and associated shifts in vegetation prevalent in the late Plio‐Pleistocene (Hopkins et al ., ; Kershaw, ) and matches the timing of diversification observed in other taxa (e.g. Joseph & Moritz, ; Schneider et al ., ; Norman et al ., ; Krosch, ; Macqueen et al ., ). Frequent shifts in vegetation allowed range expansions in some taxa and caused range contractions and local population extinctions in others (Aplin, ; Martin, ; Lukoschek et al ., ; Bowman et al ., ; Byrne et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have identified divergence across the BG (e.g. Hoskin et al ., ; Hugall et al ., ; O'Connor & Moritz, ; Moussalli et al ., ; Chapple et al ., ) but few have found divergent lineages that either abut or show a geographical disjunction to the north or south of, rather than centred on, this large dry corridor (but see Keleman & Moritz, ; Eldridge et al ., ; Macqueen et al ., ). This pattern of vicariant isolation and divergence, followed by dispersal and subsequent secondary contact probably occurred during a warm, wet period when closed forest was more widespread across the BG.…”
Section: Discussionmentioning
confidence: 97%
“…We considered this distance was a suitable compromise to maximize detection of predators which frequent areas on and close to roads (Meek, Ballard, Fleming, & Falzon, 2016) and medium-sized mammals which are likely to prefer vegetative cover (MacQueen, Seddon, & Goldizen, 2011;Norton et al, 2015). We considered this distance was a suitable compromise to maximize detection of predators which frequent areas on and close to roads (Meek, Ballard, Fleming, & Falzon, 2016) and medium-sized mammals which are likely to prefer vegetative cover (MacQueen, Seddon, & Goldizen, 2011;Norton et al, 2015).…”
Section: Survey Design and Camera Trappingmentioning
confidence: 99%
“…Solid lines indicate some of the previous published locations of the LB – 1: MacQueen et al . (), 2: Ford (), Eldridge et al . (); 3: Edwards & Melville ().…”
Section: Laura Basinmentioning
confidence: 99%
“…Furthermore, patterns in an agamid lizard that inhabits adjacent dry woodland exhibit the expected inverse effect of expansion of drier habitat in this region with evidence for stepping‐stone historical population expansion (Edwards & Melville, ). In contrast, some birds (Joseph, Moritz & Hugall, , ; Joseph & Moritz, ; Nicholls & Austin, ) and mammals (MacQueen et al ., ; Bryant & Fuller, ) show no apparent influence of the BMC on population structure (even when they were significantly structured by other nearby barriers), implying that responses to this barrier were species specific and over‐generalisation of patterns and effects may be inappropriate.…”
Section: Black Mountain Corridormentioning
confidence: 99%